Understanding the vocabulary of the nuclear arms race - Fleisher, Paul. (Minneapolis, MN : Dillon Press, 1988)
Presents definitions of terms most commonly encountered in discussio ns of the nuclear arms race.
Includes bibliographical references (p. 191-192.) and index.
Keywords: Nuclear warfare -- Dictionaries -- Juvenile literature; Nuclear warfare -- Dictionaries